2002
DOI: 10.1063/1.1424320
|View full text |Cite
|
Sign up to set email alerts
|

Statistical thermodynamics of polydisperse polymer systems in the framework of lattice fluid model: Effect of molecular weight and its distribution on the spinodal in polymer solution

Abstract: With the aid of thermodynamics of Gibbs, the expression of the spinodal was derived for the polydisperse polymer-solvent system in the framework of Sanchez-Lacombe Lattice Fluid Theory ͑SLLFT͒. For convenience, we considered that a model polydisperse polymer contains three sub-components. According to our calculation, the spinodal depends on both weight-average (M w ) and number-average (M n ) molecular weights of the polydisperse polymer, but the z-average molecular weight (M z ) dependence on the spinodal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…17 The polydispersity of polymers can also change the phase separation temperature. [35][36][37] Increase in the polydispersity index enlarges the phase separation area and shis the LCST to lower temperatures. The polydispersity effect weakens with the increase of molecular weight.…”
Section: Phase Diagram and Morphological Observationmentioning
confidence: 99%
“…17 The polydispersity of polymers can also change the phase separation temperature. [35][36][37] Increase in the polydispersity index enlarges the phase separation area and shis the LCST to lower temperatures. The polydispersity effect weakens with the increase of molecular weight.…”
Section: Phase Diagram and Morphological Observationmentioning
confidence: 99%
“…In our previous paper, the effects of polydispersity on the spinodal in polymer solutions were studied by using the Sanchez−Lacombe lattice fluid theory (SLLFT). It is well-known that the behavior of the polymer in mixtures is much different from that in solutions. However, the study in this area is limited by the complexity of the mixture, because the system may contain thousands of components.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for disperse samples the higher weight fractions have a greater influence on the cloud point. 62,63 This set us to explore the phase separation of binary polymer blends in DOP, where we used mixtures of two of different chemical composition, and thus different cloud points. The idea was to incrementally regulate the level of opacity.…”
Section: Phase Separation Behaviour Of Polystyrene In Phthalate and Nonphthalate Plasticizersmentioning
confidence: 99%